Lean Manufacturing Analysis to Minimize Waste on The Production Process - Silambi, Yobel; Indiyanto, Rus (The Indonesian Journal of Computer Science, 2024)
Improvements to eliminate or reduce non-value added activities that cause waste with Lean Manufacturing analysis on CV ABC. Lean Manufacturing is a continuous effort to eliminate (waste) and increase value add (value added) products (goods/services) to provide value to customers (customer value). Objective This research is to determine the factors that cause waste in the production process and to give proposal on company method minimize waste which has been identified. Data in this research are quantitative and qualitative data. Primary data processing in the form of standard time calculations took 30 data, which means 30 batches of fish roulade production. Lean Manufacturing Approach carried out by analyzing the flow of information and the flow of goods using the Value Stream Mapping method. Waste Which dominant happen that is time waiting, unnecessary movements and processes it is not in accordance with. Waste of time waiting occurs in process steaming. Waste time wait on process production can be minimized by adding production facilities which can reduce the dough waiting outside the machine steaming. Waste movement which no need can minimized by increased supervision from superiors as well as providing firm action to workers. Waste for non-compliant processes can be reduced by clarify standard operation Which applies in company and stick it in every production process, as well do maintenance machine in a way regular so that performance machine always deep conditions which good. Reduced time to reduce lead time ie amounting to 37.78 minutes. This time is obtained from subtraction the process of taking spices, weighing flour and vegetables as well as preparation and maximization activities process draining with addition facility. Matter this result change time leads time production from 674.44 minutes to 636.66 minutes.